Nanodiamonds: Nanodiamond‐Embedded p‐Type Copper(I) Oxide Nanocrystals for Broad‐Spectrum Photocatalytic Hydrogen Evolution (Adv. Energy Mater. 4/2016). Issue 4 (February 2016) - Lin, Zhaoyong; Xiao, Jun; Li, Lihua; Liu, Pu; Wang, Chengxin; Yang, Guowei
Abstract : The use of nanodiamonds to improve the photocatalytic hydrogen evolution reaction of Cu2 O by nanocomposition is demonstrated for the first time by Guowei Yang and co‐workers in article number 1501865. Compared with pure Cu2 O, this nanocomposite shows a tremendous improvement in performance. It is also established that the broad spectral response and electron injection from nanodiamond to Cu2 O play a dominant role.